Integrating the Interprofessional Education Practice (IEP) with an International Service Learning (ISL) to Enhance Allied Health Sciences Programs at an HBCU: The Oaxaca, Mexico Experience...National Society of Allied Health (NASH) Annual Conference (Virtual), March 4-6, 2021. - Castor, C.; Hosey, W.; Neita, M. (Journal of the National Society of Allied Health)
Current allied health education practice requires educators to address the need for improved professional collaboration, teamwork, global outreach, and effective interprofessional communication. The integration of the interprofessional education practice (IEP) model with an International Service-Learning (ISL) component was developed as a strategy to enhance the learning of minority students, build collaborative approaches to health care delivery, develop professional skills, and meet the demand of the global health workforce crisis. African American students represent approximately 5.4% of undergraduate study abroad participants. Therefore, the addition of an international internship at an HBCU will enhance their effectiveness to provide exceptional care, build their resume, and be competitive applicants for graduate and advanced certification programs. The College of Nursing and Allied Sciences (CNAHS) at Howard University designed an integrated Study Abroad activity for undergraduate and graduate students. The Pilot Program was implemented in collaboration with Universidad Del Mar, Oaxaca, Mexico, during a winter semester, as part of the University's mandate that colleges develop faculty-led Study Abroad activities for students. The Program incorporated activities for Allied Health Science departments and pre-medical students from the Department of Biology. Students interacted with individuals from several health disciplines in hospital and clinic settings, including clinical laboratories, dietary/nutritional science units, and physical and occupational therapy facilities. Despite some limitations due to the language barrier, students report a valuable exposure to other healthcare professions and the interprofessional and cultural experience. Because of the Program's success for both students and faculty, the team plans a more extensive summer semester activity in the future.